How should childhood acute lymphoblastic leukemia relapses in low‐income and middle‐income countries be managed: The AHOPCA‐ALL study group experience. Issue 5 (12th December 2022) - Espinoza, Darrell; Blanco Lopez, Jessica G.; Vasquez, Roberto; Fu, Ligia; Martínez, Roxana; Rodríguez, Hilze; Navarrete, Marta; Howard, Scott C.; Friedrich, Paola; Valsecchi, Maria Grazia; Conter, Valentino; Ceppi, Francesco
Abstract: Background: Children with relapsed acute lymphoblastic leukemia (ALL) in low‐income and middle‐income countries rarely survive. The Pediatric Hematology‐Oncology Association of Central America (AHOPCA) developed the AHOPCA‐ALL REC 2014 protocol to improve outcomes in resource‐constrained settings without access to stem cell transplantation. Methods: The AHOPCA‐ALL REC 2014 protocol was based on a modified frontline induction phase 1A, a consolidation therapy with six modified R‐blocks derived from the ALL–Berlin‐Frankfurt‐Munster REZ 2002 protocol and intermittent maintenance therapy. Children with B‐lineage ALL were eligible after a late medullary relapse, an early or late combined relapse, or any extramedullary relapses. Those with T‐lineage ALL were eligible after early and late extramedullary relapses, as were those with both B‐lineage and T‐lineage relapses occurring at least 3 months after therapy abandonment. Results: The study population included 190 patients with T‐lineage ( n  = 3) and B‐lineage ( n  = 187) ALL. Of those with B‐lineage ALL, 25 patients had a very early extramedullary relapse, 40 had an early relapse (32 extramedullary and 8 combined), and 125 had a late relapse (34 extramedullary, 19 combined, and 72 medullary). The main cause of treatment failure was second relapse (52.1%). The 3‐year event‐free survival rate (± standard error) was 25.9% ± 3.5%, and the 3‐year overall survival rate was 36.7% ± 3.8%. The 3‐year event‐free survival rate was 47.2% ± 4.7% for late relapses. The most frequently reported toxicity was grade 3 or 4 infection. Mortality during treatment occurred in 17 patients (8.9%), in most cases because of infectious complications. Conclusions: Selected children with relapsed ALL in Central America can be cured with second‐line regimens even without access to consolidation with stem cell transplantation. Children in low‐income and middle‐income countries who have lower risk relapses of ALL should be treated with curative intent. Abstract : In the context of a Central American setting, the authors describe the Pediatric Hematology‐Oncology Association of Central America acute lymphocytic leukemia (ALL) REC 2014 protocol for ALL relapse at favorable risk and its results—the first report of a second‐line protocol for ALL in low‐income and middle‐income countries. This experience suggests that, in settings like those of Central America, second‐line regimens currently used for childhood ALL relapses may be of benefit only for patients who have B‐lineage late medullary or extramedullary first relapses.